PENANGGULANGAN KECEMASAN AKADEMIK SISWA MELALUI PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Sembiring, Mimpin; Simamora, Parlaungan; Situmorang, Vinsensius M. Junior (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to examine the forms of academic anxiety experienced by students and the role of Catholic Religious Education in overcoming such anxiety at SMA Negeri SMAK Samosir. This research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. Informants included the Catholic Religious Education teacher and ten purposively selected students. The findings indicate that students’ academic anxiety manifests in three main aspects: affective, physiological, and cognitive. The affective aspect is dominated by a lack of self-confidence; the physiological aspect is marked by rapid heartbeat; and the cognitive aspect is characterized by negative thoughts. Catholic Religious Education plays a significant role in alleviating academic anxiety through the topic of